Penerapan metode guided discovery learning dengan pendekatan scientific terhadap keterampilan proses sains pada konsep Pencemaran Lingkungan di kelas X SMA Negeri 1 Ciniru Kabupaten Kuningan - Gilang Gilang; Ondi Suganda; Rahma Widiantie (Program Studi Pendidikan Biologi, FKIP Universitas Kuningan, 2015)
This research is motivated by the science process skills of students is still low, as shown by the students have difficulties in data collection in the field, students are less accurate and less scrupulous in observing and identifying data as well as the students have difficulties in recording and report the results of observations. Formulation of the problem in this study is whether there is the effect of applying the method of guided discovery learning scientific approach to the science process skills of students to the concept of Environmental Pollution in class X SMA Negeri 1 Ciniru at Kuningan Regency. The purpose of this study was to determine the effect of the application of guided discovery learning methods with the scientific approach to the science process skills of students to the concept of Environmental Pollution. The method used in this study is the experimental method. Population taken in this study was all students of class X with the number of students of 160 students. Sampling technique with simple random sampling so that students can X.2 class as a class experiment with the number of 40 students and the class as a class X.4 controls the number of 40 students. Data processing technique used is the test of normality, homogeneity test and t test. Science process skills of the experimental group students with the application of guided discovery learning method with Scientifics approach including both categories whereas the control group with conventional teaching methods, including the application of enough categories. Based on statistical calculations obtained t hits (5.373) t daf (1.67), then thank Hi means that there are significant application of guided discovery learning method with a scientific approach to the science process skills on the concept of Environmental Pollution in class X SMA Negeri 1 Ciniru at Kuningan Regency. From these results it can be concluded that the application of the method of guided discovery learning with a scientific approach to improve science process skills on the concept of Environmental Pollution in class X SMA Negeri 1 Ciniru at Kuningan Regency.Keywords: Method of guided discovery learning, scientific approach, science process skills